2020
DOI: 10.1371/journal.pone.0241000
|View full text |Cite|
|
Sign up to set email alerts
|

Eocene intra-plate shortening responsible for the rise of a faunal pathway in the northeastern Caribbean realm

Abstract: Intriguing latest Eocene land-faunal dispersals between South America and the Greater Antilles (northern Caribbean) has inspired the hypothesis of the GAARlandia (Greater Antilles Aves Ridge) land bridge. This landbridge, however, should have crossed the Caribbean oceanic plate, and the geological evolution of its rise and demise, or its geodynamic forcing, remain unknown. Here we present the results of a land-sea survey from the northeast Caribbean plate, combined with chronostratigraphic data, revealing a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…The onset of subsidence slowdown (Figure 9b) is synchronous with the late Eocene‐Oligocene compressional uplift that caused the emergence of the so‐called “GrANoLA” landmass (Greater Antilles‐Northern Lesser Antilles; Philippon et al., 2020). This subsidence slowdown also corresponds in time with the late Oligocene‐early Miocene tectonic inversion in the Grenada Basin, which preceded the emplacement of the Miocene to Recent southern southern Lesser Antilles Arc (see previous section).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of subsidence slowdown (Figure 9b) is synchronous with the late Eocene‐Oligocene compressional uplift that caused the emergence of the so‐called “GrANoLA” landmass (Greater Antilles‐Northern Lesser Antilles; Philippon et al., 2020). This subsidence slowdown also corresponds in time with the late Oligocene‐early Miocene tectonic inversion in the Grenada Basin, which preceded the emplacement of the Miocene to Recent southern southern Lesser Antilles Arc (see previous section).…”
Section: Discussionmentioning
confidence: 99%
“…To the west, at the Saba Bank, two unconformities are observed in SB2 well, Oil company MCS lines (Church & Allison, 2004), and lines GA15B‐C‐GA08 (Figure 6) recorded during the GARANTI cruise (Cornée et al., 2019; Lebrun & Lallemand, 2017; Philippon, Cornée, et al., 2020; Philippon, van Hinsbergen, et al., 2020 #2812). From Church and Allison (2004), a late Eocene unconformity S3 separates an undrilled basement unit topped by middle Priabonian andesitic lavas flows overlaid by a very late Eocene to early Oligocene Lower Carbonate and Turbiditic unit.…”
Section: Tectonic Evolution Of the Nla Forearcmentioning
confidence: 99%
“…A lower boundary age for U1 can be proposed. At St Barthélemy and in the backarc, compressional tectonic structures are sealed by a late Priabonian unconformity (Church & Allison, 2004; Philippon, Cornée, et al., 2020). Following this compression, the Kalinago Basin opening and extensive evidences in the Northern Anguilla Bank attest for a regional extension during the early Oligocene to early Miocene characterized by synsedimentary half‐grabens (Cornée et al., 2019; Legendre et al., 2018).…”
Section: Tectonic Evolution Of the Nla Forearcmentioning
confidence: 99%
“…In this work, we study the palaeogeographic evolution of the northeastern part of the Lesser Antilles during the Cenozoic, as it may have constituted an episodic emerged area between the Aves Ridge to the southwest and the Greater Antilles to the North: the GrANoLA land -Greater Antilles-Northern Lesser Antilles land (Philippon et al, 2020a). Previous bathymetric reconstructions and offshore-onshore geological investigations have suggested that the Kalinago intra-arc rift basin (Figs.…”
Section: Introductionmentioning
confidence: 99%